2017
DOI: 10.33425/2639-9326.1019
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Anti-Diabetic Therapy in Women with Diabetes in Pregnancy

Abstract: Background: Hyperglycemia in pregnancy is associated with adverse pregnancy outcomes. Strict glycaemic control is necessary to promote favourable pregnancy outcomes. Objectives: To assess adherence to anti-diabetic therapy (diet, physical activity and medications) in women with diabetes in pregnancy. Methods: This study utilized a cohort of 157 pregnant women at three Central hospitals in Zimbabwe. Adherence to anti-diabetic therapy was the exposure and the outcomes of interest were maternal and perinatal outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although self-reported measures were the main tools for estimating medication adherence in this review [18-26, 28, 29], some studies assessed fasting blood glucose or glycated haemoglobin as a means of confirming adherence and predicting disease outcomes [18,22,28]. Generally, adherence to oral antidiabetic medications and insulin has been found to range between 36-93% and 62-64%, respectively [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although self-reported measures were the main tools for estimating medication adherence in this review [18-26, 28, 29], some studies assessed fasting blood glucose or glycated haemoglobin as a means of confirming adherence and predicting disease outcomes [18,22,28]. Generally, adherence to oral antidiabetic medications and insulin has been found to range between 36-93% and 62-64%, respectively [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The dominant medications used in the management of gestational diabetes according to the papers reviewed were insulin [18,[20][21][22][23][24] and metformin [19,21,22,25]. Besides medications, adherence to lifestyle/behaviours like self-monitoring of blood glucose levels, dietary therapy, and physical activity were considered [18,20,[22][23][24][25][26][27][28]. Self-report measures were the recorded means of estimating adherence [18-26, 28, 29].…”
Section: Types Of Medications and Adherencementioning
confidence: 99%
“…This is much less than the results of a hospital-based study in Zimbabwe (66.8%) on dietary adherence. [ 18 ] This difference in results may be due to the use of different study tools. This indicates that we will have to work more on the monitoring of dietary adherence among antenatal women with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Using OpenEpi version 3.01, a study conducted in Zimbabwe reported the adherence rate to diet therapy was 66.8%. [ 18 ] Assuming the same prevalence, absolute precision of 5%, and 95% confidence interval (CI), the calculated sample size was 341. Universal sampling was done to include the eligible participants.…”
Section: Methodsmentioning
confidence: 99%